The Effect Of Simaster Use On The Academic Values Of Semester 5 Students Faculty Of Tarbiyah University Of Al-Amien Prenduan Sumenep Madura 2024 - Tri Hardiyanti; Abd Qodir Jailani (Responsive: Jurnal Manajemen Pendidikan Islam, 2025)
Islamic education in the modern era faces significant challenges in integrating traditional values ​​with technological advances. One interesting context to research is Al-Amien Prenduan University, which is an Islamic educational institution but is also open to digital-based educational innovations such as the use of SIMASTER which is used as a supporting medium in cognitive aspects, especially for searching for information relevant to coursework and learning. The aim of this research is to determine whether there is an influence of using SIMASTER on the academic grades of students at the Tarbiyah Faculty of Al-Amien Prenduan University for the 2024 academic year. Research method: quantitative approach survey. Analysis method: simple linear regression. Research results: Based on the provisions above, the level of correlation between the two variables found at 0.803 is in the high category. So there is a high correlation between the influence of using SIMASTER on the academic grades of 5th semester students at the Faculty of Tarbiyah, Al-Amien Prenduan University. Conclusion: H1 is accepted, there is a significant influence between the use of SIMASTER on the academic grades of students in the 5th semester of the Faculty of Tarbiyah, Al-Amien Prenduan University, Sumenep Madura 2024. And H0 is rejected, there is no use of SIMASTER on the academic grades of students in the 5th semester of the Faculty of Tarbiyah, Al-Amien Prenduan University, Sumenep Madura 2024.